Women’s Portrayals in the Comic Books (A Visual Grammar of the Heroines’ Portrayals in the Selected Comic Books Published by Dc Comics and Marvel) - Sani Satya Pratiwi (Passage, 2013)
This paper entitled “Women’s Portrayals in the Comic Books (A Visual Grammar of the Heroines’ Portrayals in the Selected Comic Books Published by DC Comics and Marvel)” is aimed at investigating how women, especially heroines are portrayed in the comic books and what the portrayals signify. The study is a qualitative study using the visual grammar theory proposed by Kress and van Leeuwen (2006) and the systemic functional linguistics theory proposed by Halliday (2004). The data are in the form of four online comics published by DC Comics and Marvel. The study finds that heroines are portrayed in negative and positive ways. The negative ways portray the heroines as sex symbols, the ones who sexually stimulate men’s attention in their appearance, greedy, fragile (especially when the heroines play their character as alter ego). While, the positive ways portray the heroines as strong, brave, smart and impressive ones. The findings also show that no matter how strong the heroines, they are still in the subjection. Keywords: Portrayal, Comic Books, Heroines, Visual Grammar